Hubungan Perilaku Gaya Hidup dengan Peningkatan Tekanan Darah Pada Lansia di Gereja Katolik Paroki Santo Paulus Pasar Merah Medan Tahun 2021 - Josua Fransiskus Sirait; Imelda Derang; Lilis Novitarum (JINTAN: Jurnal Ilmu Keperawatan, 2022)
Background: Hypertension or the condition of increasing systolic and diastolic blood pressure, namely 140 mmHg/≥90 mmHg, is susceptible to the elderly. Lifestyle can be a trigger factor for hypertension, such as diet, physical activity, smoking habits and sleep patterns. There is a relationship between lifestyle behavior and increased blood pressure. Methods: This type of descriptive correlation research with cross sectional approach method, total sampling sampling technique, the number of samples is 60 people. The instruments used in this study were lifestyle questionnaires and observation sheets. Results: The results showed that there was a relationship between lifestyle behavior and increased blood pressure in the elderly at the Catholic Church of the Santo Paulus Parish, Pasar Merah Medan. Conclusion: It can be concluded that there is a relationship between lifestyle behavior and increased blood pressure in the elderly at the St Paul's Parish Catholic Church, Pasar Merah Medan. It is hoped that the elderly will regularly control their blood pressure at the nearest health service such as health centers, posyandu and hospitals.